Faktor-faktor yang Mempengaruhi Kinerja Keuangan Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Riris Kharisma; Kartika Hendra Titisari; Suhendro Suhendro (Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of good corporate governance, corporate social responsibility, leverage and company size on the financial performance of state-owned companies listed on the IDX. The data in this study use secondary data. The population in the study of all BUMN companies listed on the IDX for the 2015-2019 period. The sample used in this study was 9 samples of BUMN companies listed on the IDX for the 2015-2019 period, with the sampling method using purposive sampling method. The test method in this study uses multiple linear regression test. The results show that good corporate governance, leverage and company size affect the financial performance of BUMN companies listed on the IDX for the 2015-2019 period, on the other hand, corporate social responsibility does not affect the financial performance of BUMN companies listed on the IDX for the 2015-2019 period. had no effect on the financial performance of BUMN companies listed on the IDX for the 2015-2019 period.